Lenalidomide in combination with gemcitabine as first-line treatment for patients with metastatic carcinoma of the pancreas: A Sarah Cannon Research Institute phase II trial - Infante, Jeffrey R. (Landes Bioscience, 2013)
Objectives: To evaluate the 6-mo overall survival, safety and tolerability of lenalidomide in combination with standard gemcitabine as first-line treatment for patients with metastatic pancreatic cancer. Methods: Eligibility included: previously untreated metastatic adenocarcinoma of the pancreas with metastases incurable by surgery/radiation therapy; ECOG PS 0–2; adequate organ function; prophylactic anticoagulation for venous thromboembolic events (VTEs). Patients received lenalidomide 25 mg PO (days 1–21) and gemcitabine 1,000 mg/m(2) IV (days 1, 8 and 15) each 28-day cycle, with response evaluations every eight weeks. Results: Between 5/2009–4/2010, 72 patients (median age 64 years; 68% male; 42% ECOG PS 0) were enrolled in this multicenter, community-based study. Six-month OS was 37% (95% CI 26–48%). Median PFS and OS were 2.3 (95% CI 1.9–3.5) and 4.7 (95% CI 3.4–5.7) months, respectively. Eight partial responses (11%) were documented. Thirty-nine patients (54%) experienced thrombocytopenia (2 patients, 3% grade 4). Hematologic toxicities resulted in dose modifications for the majority of patients. Twenty patients (28%) developed VTEs during treatment. Conclusions: The observed 6-month OS (37%) of lenalidomide with gemcitabine does not suggest improvement compared with historical results with gemcitabine alone. Toxicities and dose modifications likely limited dose intensity. Further development of this regimen in pancreas cancer is not recommended.